Long-Term Health Insurance: Theory Meets Evidence - Juan Pablo Atal; Hanming Fang; Martin Karlsson; Nicolas R. Ziebarth (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2020)
To insure policyholders against contemporaneous health expenditure shocks and future reclassification risk, long-term health insurance constitutes an alternative to community-rated short-term contracts with an individual mandate. Relying on unique claims panel data from a large private insurer in Germany, we study a real-world long-term health insurance application with a life-cycle perspective. We show that German long-term health insurance (GLTHI) achieves substantial welfare gains compared to a series of risk-rated short-term contracts. Although, by its simple design, the premium setting of GLTHI contract departs significantly from the optimal dynamic contract, surprisingly we only find modest welfare differences between the two. Finally, we conduct counterfactual policy experiments to illustrate the welfare consequences of integrating GLTHI into a system with a "Medicare-like" public insurance that covers people above 65.
Keywords: G22; I11; I18; 330; Long-Term Health Insurance; Individual Private Health Insurance; Health Care Reform